Synthesis, characterization, and crystal structures of oxidovanadium(V) complexes derived from similar hydrazone and benzohydroxamate mixed ligands. Issue 7 (3rd July 2017) - Qian, Shao-Song; Cheng, Xiao-Shan; You, Zhonglu; Zhu, Hai-Liang
ABSTRACT: Two new oxidovanadium(V) complexes with the general formula [VOL(bha)], where L represents the deprotonated hydrazone ligands 2-hydroxy- N' -(4-methoxybenzylidene)naphthohydrazide (H2 L 1 ) for1 and N' -(2-chlorobenzylidene)-2-hydroxynaphthohydrazide (H2 L 2 ) for2, and bha represents the monoanionic form of benzohydroxamic acid (Hbha), have been prepared and characterized by elemental analysis, infrared and UV-Vis spectra, and thermal behavior. Structures of the complexes have been further determined by single-crystal X-ray diffraction. The V atoms in the complexes are coordinated by the three donor atoms of the hydrazone ligands, the oxygen atoms of the benzohydroxamate ligands, and oxido oxygen atoms, constituting octahedral coordination spheres.